A Bookish Intervention: Thomas Bewick's British Birds and the Reconfiguration of Illustrated Natural History. Issue 1 (April 2021) - Ferris, Ina
Abstract : This essay argues that the impact of Bewick's natural histories on nineteenth-century reading culture owed not simply to their engravings but to an innovative manipulation of the affordances of the material form of the book-volume. Governed by a commitment to the printed book as a formative medium in the making of reading relations, Bewick reconfigured the fundamental unit of illustrated natural history, the double-structured unit of description, and altered the dynamics of natural history reading. Repositioning readers so as to bring them into closer proximity both to the book and to the natural world around them, his celebrated bird book brings into view often overlooked linkages between the period's intensified bookishness, emergent knowledge fields, the reading public, and generic innovation that were to reshape the culture of reading in the nineteenth century.